2007
DOI: 10.1289/ehp.9686
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Arsenic Exposure and Cardiac Repolarization Abnormalities with QT Interval Prolongation in a Population-based Study

Abstract: BackgroundChronic arsenic exposure is associated with cardiovascular abnormalities. Prolongation of the QT (time between initial deflection of QRS complex to the end of T wave) interval and profound repolarization changes on electrocardiogram (ECG) have been reported in patients with acute promyelocytic leukemia treated with arsenic trioxide. This acquired form of long QT syndrome can result in life-threatening arrhythmias.ObjectiveThe objective of this study was to assess the cardiac effects of arsenic by inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 33 publications
3
81
4
Order By: Relevance
“…As exposure in a wide range of levels is consistently associated with QT prolongation -a risk factor for arrhythmia and sudden cardiac death -torsade de pointes (Ficker et al 2004;Mumford et al 2007;Mordukhovich et al 2009;Wang et al 2009), and increased QT dispersion (Wang et al 2010). As may act on QT by increasing cardiac calcium currents (Ficker et al 2004), but no protective effect of calcium-antagonists has been found (Mordukhovich et al 2009) and there are conflicting data on verapamil enhancing or reducing As cardiotoxicity (Zhao et al 2008a;Luong and Rabkin 2009).…”
Section: Other Mechanisms Of CV Damagementioning
confidence: 99%
“…As exposure in a wide range of levels is consistently associated with QT prolongation -a risk factor for arrhythmia and sudden cardiac death -torsade de pointes (Ficker et al 2004;Mumford et al 2007;Mordukhovich et al 2009;Wang et al 2009), and increased QT dispersion (Wang et al 2010). As may act on QT by increasing cardiac calcium currents (Ficker et al 2004), but no protective effect of calcium-antagonists has been found (Mordukhovich et al 2009) and there are conflicting data on verapamil enhancing or reducing As cardiotoxicity (Zhao et al 2008a;Luong and Rabkin 2009).…”
Section: Other Mechanisms Of CV Damagementioning
confidence: 99%
“…In one study, more than 40% of patients reported that the primary reason for missing a dose of DFO was drug-related side effects [14]. Additionally, the mode of DFO administration – subcutaneous infusions over an 8- to 12-hour period, 5–7 days per week [15] – is extremely demanding.…”
Section: Introductionmentioning
confidence: 99%
“…However, as has long been acknowledged in chemistry and toxicology, chronic arsenic intoxication might induce lesions to multiple organs and systems, involving the liver, skin, cardiovascular, neurologic and GI systems [79,80], and the most frightful adverse effect is carcinogenesis occurring specifically on the skin, lungs and bladder [80]. Smith et al [81] estimated that the lifetime risk of dying from cancer generated by daily ingestion of 1 l of water containing 50 lg/l arsenic could be as high as 13 per 1000 people exposed.…”
Section: Relapse In Apl Including Cns Relapsementioning
confidence: 99%